Evaluation of the Differences Between Conventional and Digitally Developed Models Used for Prosthetic Rehabilitation in a Case of Untreated Palatal Cleft. (March 2021) - Beh, Yew Hin; Farook, Taseef Hasan; Jamayet, Nafij Bin; Dudley, James; Rashid, Farah; Barman, Aparna; Alam, Mohammad Khursheed
Objective: The virtual cone beam computed tomography–derived 3-dimensional model was compared with the scanned conventional model used in the fabrication of a palatal obturator for a patient with a large palatal defect. Design: A digitally derived 3-dimensional maxillary model incorporating the palatal defect was generated from the patient's existing cone beam computerized tomography data and compared with the scanned cast from the conventional impression for linear dimensions, area, and volume. The digitally derived cast was 3-dimensionally printed and the obturator fabricated using traditional techniques. Similarly, an obturator was fabricated from the conventional cast and the fit of both final obturator bulbs were compared in vivo. Results: The digitally derived model produced more accurate volumes and surface areas within the defect. The defect margins and peripheries were overestimated which was reflected clinically. Conclusion: The digitally derived model provided advantages in the fabrication of the palatal obturator; however, further clinical research is required to refine consistency.